Reconceptualising risk: Perceptions of risk in rural and remote maternity service planning. (July 2016) - Barclay, Lesley; Kornelsen, Jude; Longman, Jo; Robin, Sarah; Kruske, Sue; Kildea, Sue; Pilcher, Jennifer; Martin, Tanya; Grzybowski, Stefan; Donoghue, Deborah; Rolfe, Margaret; Morgan, Geoff
Abstract: Objective: to explore perceptions and examples of risk related to pregnancy and childbirth in rural and remote Australia and how these influence the planning of maternity services. Design: data collection in this qualitative component of a mixed methods study included 88 semi-structured individual and group interviews ( n =102), three focus groups ( n =22) and one group information session ( n =17). Researchers identified two categories of risk for exploration: health services risk (including clinical and corporate risks) and social risk (including cultural, emotional and financial risks). Data were aggregated and thematically analysed to identify perceptions and examples of risk related to each category. Setting: fieldwork was conducted in four jurisdictions at nine sites in rural ( n =3) and remote ( n =6) Australia. Participants: 117 health service employees and 24 consumers. Measurements and findings: examples and perceptions relating to each category of risk were identified from the data. Most medical practitioners and health service managers perceived clinical risks related to rural birthing services without access to caesarean section. Consumer participants were more likely to emphasise social risks arising from a lack of local birthing services. Key conclusions: our analysis demonstrated that the closure of services adds social risk, which exacerbates clinical risk. Analysis also highlighted that perceptions of clinical risk are privileged over social risk in decisions about rural and remote maternity service planning. Implications for practice: a comprehensive analysis of risk that identifies how social and other forms of risk contribute to adverse clinical outcomes would benefit rural and remote people and their health services. Formal risk analyses should consider the risks associated with failure to provide birthing services in rural and remote communities as well as the risks of maintaining services. Highlights: Perceptions of risk influence rural and remote maternity service planning. Perceptions of clinical risk are privileged over other types of risk. Closure of rural maternity services creates social risk for women and infants. Social risk exacerbates clinical risk and therefore contributes to overall risk.